Massive saddle embolism in chronic thromboembolic pulmonary hypertension: The unresolved tale - Firdaus, Achmad Jauhar; Karolina, Wella (Heart Science Journal, 2025)
BACKGROUND: Chronic thromboembolic pulmonary hypertension (CTEPH) represents a rare and severe variant of pulmonary hypertension (PH), leading to progressive damage to the cardiopulmonary system. The obstruction could happen anywhere from the small branches to the main pulmonary artery. A saddle-type emboli, a particularly severe type of pulmonary embolism that occurs in the main pulmonary artery and blocks both the right and left branches, has the highest potential to cause death. This article presents a case of progressive CTEPH with inoperable conditions that underwent catheter-directed thrombolysis (CDT) as a last resort given the limitations of other treatment modalities. CASE: A 53-year-old woman with worsening shortness of breath was diagnosed with CTEPH, but despite anticoagulant treatment, imaging evaluation showed a progressive saddle-type pulmonary embolism along with findings of interstitial lung disease (ILD). Multidisciplinary team discussions were conducted, and the decision to proceed with pulmonary endarterectomy (PEA) was influenced by various factors. CDT was then performed, however, there was no notable clinical improvement. The patient ultimately succumbed to the disease following 31 days of treatment. CONCLUSION: CTEPH is a rare type of pulmonary hypertension caused by pulmonary embolism. The treatment algorithm employs a multimodal strategy that addresses the different anatomical lesions. In proximal obstruction, surgical PEA remains the treatment of choice in operable patients. An experienced multidisciplinary team is mandatory. Without these requirements, other strategies can continue to be studied for their role in inoperable CTEPH.